Trends in cyclical food expenditures among low-income households receiving monthly nutrition assistance: results from a prospective study. Issue 3 (16th February 2021) - Valluri, Sruthi; Mason, Susan M; Peterson, Hikaru H; French, Simone A; Harnack, Lisa J
Abstract: Objective: Supplemental Nutrition Assistance Program (SNAP) benefits are rapidly depleted after distribution. This phenomenon, known as the benefit cycle, is associated with poor nutrition and health outcomes. However, to date, no study has evaluated trends in food expenditures before and after households receive benefits using prospective data, and whether these trends vary by household characteristics. Design: Generalised estimating equations were used to model weekly household food expenditures during baseline (pre-benefit) and intervention months by vendor (restaurants and food retailers). Food retailer expenditures were further evaluated by food category (fruits and vegetables and foods high in added sugar). All expenditures were evaluated by household composition, demographics and economic means. Setting: Minneapolis-St. Paul, Minnesota, metropolitan area. Participants: Low-income households ( n 249) enrolled May 2013–August 2015. Results: Weekly food retailer expenditures did not vary during baseline (pre-benefit), but demonstrated a cyclical pattern after households received benefits across all household characteristics and for both food categories, particularly for fruits and vegetables. Households with greater economic resources spent more throughout the month compared with those with fewer resources. Households with lower food security status experienced more severe fluctuations in spending compared with more food secure households. Conclusions: Cyclical food purchasing was observed broadly across different household characteristics and food categories, with notable differences by household economic means and food security status. Proposed SNAP policy changes designed to smooth food expenditures across the benefit month, such as increased frequency of benefit distribution, should include a focus on households with fewest resources.